Exchange Rate Responses to Inflation in Bangladesh - Hossain, Akhtar (IMF Working Papers; Working Paper, 2002)
This paper investigates the exchange rate responses to inflation in Bangladesh during the period from 1972-73 to 1999. Both annual and monthly data are used in the investigation. The results suggest that past consumer price inflation generally led to currency devaluation, measured as a decline in the value of the currency in terms of the trade-weighted nominal effective exchange rate. The effect of inflation on devaluation, however, became weaker following the financial reforms undertaken in the early 1980s. The effect of devaluation on inflation was not significant, and this result remained robust throughout the sample period.